Research Note: Evaluation of microbial contamination on broiler carcasses – an investigation of body parts and sampling methods - Bastian Wyink; Alina Kirse; Felix Reich (Poultry Science, 2025)
We investigated whether samples of the neck skin from 24 broiler chickens, which were taken from broiler carcasses after chilling, are representative for the microbiological load (TVC – total viable count 3.99 log10 cfu/g, E. coli 2.06 log10 cfu/g, Campylobacter spp. 2.04 log10 cfu/g) of the entire skin. No significant difference was found between the contamination of the neck skin and the other skin areas analysed (back, breast, abdominal and leg skin) for any of the target germs. We also compared results from two sampling methods (neck skin excision and whole carcass rinse) to check whether both methods yield comparable results. Significantly higher mean values were found for the TVC in the whole carcass rinse samples (4.61 log10 cfu/ml vs. 4.28 log10 cfu/g), while we found no significant difference between both sampling methods for E. coli. For Campylobacter spp. the neck skin samples showed significantly higher mean values than the whole carcass rinse samples (2.04 log10 cfu/g vs. 1.31 log10 cfu/ml).